Faktor Predisposisi, Pencegahan dan Perilaku Sembuh Pasien Tuberkulosis Paru - Sopian Solihin; Lintang Alifah (Syntax Corporation Indonesia, 2021)
Based on data, Ministry of Health (Dinkes) Tangerang Regency, from January to March 2019 IR (insident rate) 252 for 100,000 inhabitants, the number of patients with TUBERCULOSIS reaches 6,500 people. The number of sufferers, up compared to 2018 who reached 3,838 people. This Literature review aims to view and review related articles on predisposition factors, prevention and behavior of healthy lung TB patients. This research is a method of study of libraries or literature review. Search for articles using search engine Google search engines (Google scholar, repository), Pubmed/Medline and Researchgate with PRISMA search strategy. Search articles by publication year 2015 to 2019. Results: of 15 Articles of Analytanisi derived that the dominant predisposition factor is knowledge, smoking attitude, economic status that affects the status of nutrition or nutritional intake and support of the family. In variable prevention found that prevention is done by throwing phlegm/spit in the toilet, familiarize the behavior of clean and healthy life (PHBS) in the household, regular exercise, not smoking as well as the practice of closing the mouth and nose when coughing and sneezing. In addition, opening the window for the house to get sunlight and fresh air and drying the sleeping mat so as not to be moist should be done. Meanwhile, in the behavior of recovering patients compliance with medication and prevention carried out will affect lung patients cure.